Screening study on hemolysis suppression effect of an alternative plasticizer for the development of a novel blood container made of polyvinyl chloride. Issue 4 (24th October 2013) - Haishima, Yuji; Kawakami, Tsuyoshi; Hasegawa, Chie; Tanoue, Akito; Yuba, Toshiyasu; Isama, Kazuo; Matsuoka, Atsuko; Niimi, Shingo
Abstract The aim of this study is to identify a plasticizer that is effective in the suppression of the autohemolysis of the stored blood and can be used to replace di(2‐ethylhexyl) phthalate (DEHP) in blood containers. The results of hemolysis test using mannitol‐adenine‐phosphate/red cell concentrates (MAP/RCC) spiked with plasticizers included phthalate, phthalate‐like, trimeliate, citrate, and adipate derivatives revealed that di‐isononyl‐cyclohexane‐1, 2‐dicarboxylate (Hexamoll® DINCH), di(2‐ethylhexyl)‐1, 2, 3, 6‐tetrahydro‐phthalate (DOTP), and diisodecyl phthalate (DIDP) exhibited a hemolysis suppression effect almost equal to that of DEHP, but not other plasticizers. This finding suggested that the presence of 2 carboxy‐ester groups at the ortho position on a 6‐membered ring of carbon atoms may be required to exhibit such an effect. The hemolytic ratios of MAP/RCC‐soaked polyvinyl chloride (PVC) sheets containing DEHP or different amounts of DINCH or DOTP were reduced to 10.9%, 9.2–12.4%, and 5.2–7.8%, respectively (MAP/RCC alone, 28.2%) after 10 weeks of incubation. The amount of plasticizer eluted from the PVC sheet was 53.1, 26.1–36.5, and 78.4–150 µg/mL for DEHP, DINCH, and DOTP, respectively. PVC sheets spiked with DIDP did not suppress the hemolysis induced by MAP/RCC because of low leachability (4.8–6.0 µg/mL). These results suggested that a specific structure of the plasticizer and the concentrations of least more than ∼10 µg/mL were required to suppress hemolysis due to MAP/RCC. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 102B: 721–728, 2014.